Macro-economic determinants of property-tax revenue in South Africa - Hlengwa, Samukelisiwe (Graduate School of Business (GSB), 2021)
The South African local governments are facing enormous issues that challenge their financial independence and the fulfilment of their constitutional powers in providing service delivery to communities within their jurisdiction areas, amongst other things. Although the National government provides grants to the local governments, they are not sufficient to meet the basic needs of communities within sub-national provinces – given the rapid growth in population and the high levels of unemployment. Property tax is one of the sources of municipalities' revenues, over which the local governments have full autonomy. A vast number of scholars in literature emphasize the potential and the importance of property tax revenues within local government spheres, its contribution towards the improvement of community lives, and in providing the public infrastructures with the services they require – if they are fully utilised. This study examines the impact of macro-economic factors (gross domestic product, inflation, the unemployment rate, and the population rate) on property-tax revenues in South African municipalities across the nine provinces, from the year 2005 to 2018. The panel-data model was estimated by using fixed and random effect-estimation techniques. The findings provide evidence to suggest that there is a negative and positive relationship between property tax revenues and macro-economic determinants, depending on each subcategory from which the total property-tax revenue is based. The main results of the study indicate that the variation in economic activities does not improve property-tax revenue mobilization across South African local governments. Inflation was found to have a discouraging impact on the property-tax revenues derived by municipalities. Although the population rate reflected a stable trend during the study period, the results indicated that it has had a negative impact on property-tax revenues. Generally, the unemployment rate has depicted an unstable trend over the study period; and the findings show that it has had a negative effect on property-tax revenues across South African municipalities. The study suggests some policy recommendations for achieving optimal property-tax revenues. In addition, the study has contributed to the body of knowledge; and it has provided an analysis of the various macro-economic determinants – by sing widely accepted indicators in an emerging market. This research also recommends further exploration of the impact of other macro-economic determinants on property-tax revenues, in any future research studies. These include macro-economic determinants, such as the interest rate and household income, amongst other issues, which are not part of this study.